A randomized controlled trial comparing a standard postoperative diet with low‐volume high‐calorie oral supplements following colorectal surgery. (30th July 2013) - Sharma, M.; Wahed, S.; O'Dair, G.; Gemmell, L.; Hainsworth, P.; Horgan, A. F.
Abstract: Aim: Postoperative oral nutritional supplementation is becoming a part of most patient care pathways. This study examined the effects of low‐volume high‐calorie prescribed supplemental nutrition on patient outcome following elective colorectal surgery. Method: Patients undergoing elective colorectal resections were randomized to a prescribed nutritional supplementation group (SG) [standard diet + 6 × 60 ml/day of Pro‐Cal (60 ml = 200 kcal + 4 g protein)] or conventional postoperative diet group (CG) (standard diet alone). Preoperative and daily postoperative hand‐grip strengths were measured using a grip dynamometer after randomization. Daily food intake, return of bowel activity, nausea score for the first 3 days and postoperative length of hospital stay (LOS) were prospectively recorded. Micro‐diet standardized software was used to analyse food diaries. Nonparametric tests were used to analyse the data. Results: Fifty‐five patients were analysed (SG 28, CG 27). There was no difference in median preoperative and postoperative handgrip strengths at discharge within each group (SG 31.7 vs 31.7 kPa, P  =   0.932; CG 28 vs 28.1 kPa, P  =   0.374). The total median daily calorie intake was higher in SG than CG (SG 818.5 kcal vs CG 528 kcal; P  =   0.002). There was no difference in median number of days to first bowel movement (SG 3 days vs CG 4 days, P  =   0.096). The median LOS was significantly shorter in SG than CG (6.5 vs 9 days; P  =   0.037). Conclusion: Prescribed postoperative high‐calorie, low‐volume oral supplements in addition to the normal dietary intake are associated with significantly better total daily oral calorie intake and may contribute to a reduced postoperative hospital stay.